Hitler's Wave-Breaker Concept : an Analysis of the German End Game in the Baltic. - Lunde, Henrik (Casemate, 2013)
Among the many controversies of World War II, prominent is the debate over Germany's strategy in the north of the Soviet Union, as the tide of war turned, and gigantic Russian armies began to close in on Berlin. In this long-awaited work, Henrik Lunde-former U.S. Special Forces officer and author of renowned previous works on the campaigns in Norway and Finland-turns his sights to the withdrawal of Army Group North. Providing cool-headed analysis to the problem, the author first acknowledges that Hitler-often accused of holding onto ground for the sake of it-had valid reasons in this instance t.